Comparing Performances of Evolutionary Algorithms on the Emission Dispatch and Economic Dispatch Problem - A.N. Afandi; Irham Fadlika; Andoko Andoko (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
Evolutionary methods dominate in the computation for breaking out the real problems. For a couple of years, it is more popular than classical methods for solving many cases. Technically, one of real problems is the emission dispatch and economic dispatch (EDED) problem. The EDED problem is used to optimize the power system operation (PSO) at a certain time under some constraints. This paper presents performance comparison between Harvest Season Artificial Bee Colony (HSABC) and Genetic Algorithms on the EDED problem applied to the IEEE-62 bus system. Simulation results show that the tested methods have difference characteristics and abilities for optimizing the PSO based on the EDED problem.